2006
DOI: 10.1182/blood-2006-04-017988
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of bypassing agents in hemophilia complicated by an inhibitor: the FEIBA NovoSeven Comparative (FENOC) Study

Abstract: The development of inhibitory antibodies to factor VIII is a serious complication of hemophilia. FEIBA (factor VIII inhibitorbypassing activity), an activated prothrombin complex concentrate (aPCC), and NovoSeven, recombinant factor VIIa (rFVIIa), are used as hemostatic bypassing agents in treating patients with inhibitors. The FENOC study was designed to test equivalence of the products in the treatment of ankle, knee, and elbow joint bleeding. A prospective, open-label, randomized, crossover, equivalency des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
410
0
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 415 publications
(435 citation statements)
references
References 22 publications
15
410
0
10
Order By: Relevance
“…Both agents control approximately 80% of bleeding episodes in patients with hemophilia and inhibitors. 4 Nonetheless, their hemostatic efficacy is difficult to predict and does not result in the success rates obtained with factor VIII replacement in patients who have hemophilia without inhibitors. 5 Consequently, patients with inhibitors are at increased risk for bleeding that is difficult to control.…”
Section: Discussionmentioning
confidence: 99%
“…Both agents control approximately 80% of bleeding episodes in patients with hemophilia and inhibitors. 4 Nonetheless, their hemostatic efficacy is difficult to predict and does not result in the success rates obtained with factor VIII replacement in patients who have hemophilia without inhibitors. 5 Consequently, patients with inhibitors are at increased risk for bleeding that is difficult to control.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of this much improved but still relatively unsatisfactory background, two approaches have substantially changed the picture: the development of recombinant activated factor VII (rFVIIa) as a new bypassing product and the use of immune tolerance to eradicate the inhibitor, a treatment already pioneered in the early 1980. rFVIIa can stop 80-90% of the spontaneous haemorrhages, particularly when administered early in the home setting [32,33], and elective orthopaedic surgery can be carried out safely [34,35]. The advent of rFVIIa also prompted more studies on FEIBA, which was found to be similar in efficacy and safety to rFVIIa in the context of a randomized trial [36]. One of the limits associated with the use of rFVIIa, i.e.…”
Section: From the 1990s Until Now: A New Golden Eramentioning
confidence: 99%
“…41 rfVIIa and FEIBA VH have similar efficacy and rates of thrombosis; however, in a prospective randomized comparison of rfVIIa and FEIBA VH, approximately 30% of subjects responded more favorably to one product or the other 6 and 12 hours after treatment. 42 To better tailor treatment in individual patients some have looked to thromboelastography and endogenous thrombin potential. Unfortunately, clinical studies linking these tests with clinical outcomes are lacking 7,43 ; therefore, treatment with rfVIIa and FEIBA VH must be adjusted according to clinical outcomes rather than laboratory testing results.…”
Section: Treatment Of Acute Bleedingmentioning
confidence: 99%